Towards Conservation of Genetic Variation of Tropical Tree Species With Differing Successional Status: The Case of Mansonia altissima A. Chev and Triplochiton scleroxylon K. Schum. (August 2019) - Akinnagbe, Akin; Gailing, Oliver; Finkeldey, Reiner; Lawal, Amadu
Two important West African timber tree species with differing successional status, Mansonia altissima A. Chev and Triplochiton scleroxylon K. Schum were investigated in this study. Triplochiton scleroxylon is a pioneer species found in open forests, whereas Mansonia altissima is a nonpioneer light-demanding tree species occurring in closed forests. Amplified fragment length polymorphism markers were used to compare the genetic diversities of these two timber species in stands with different degrees of human impact (isolated forest patch, logged forest, farmland, plantation, and primary forest). Contrasting effects of human impact on genetic diversity were detected for these two timber species. The results suggested severe effects of human impact on the genetic diversity of Mansonia altissima, a nonpioneer species. However, no adverse effect was recorded in Triplochiton scleroxylon, a pioneer species. These findings indicate that nonpioneer tree species could be more prone to genetic erosion than pioneer tree species as a result of adverse human impacts. Therefore, conservation of genetic diversity in both pioneer and nonpioneer tree species populations would likely necessitate different measures.